Transfection of bovine fetal fibroblast with polyethylenimine (PEI) nanoparticles: effect of particle size and presence of fetal bovine serum on transgene delivery and cytotoxicity - Forcato, Diego Oscar (2017)
The development of efficient transfection protocols for livestock cells is crucial for implementation of cell-based transgenic methods to produce genetically modified animals. We synthetized fully deacylated linear 22, 87 and 217 kDa polyethylenimine (PEI) nanoparticles and compared their transfection efficiency and cytotoxicity to commercial branched 25 kDa PEI and linear 58 kDa poly(allylamine) hydrochloride. We studied the effect of PEI size and presence of serum on transfection efficiency on primary cultures of bovine fetal fibroblasts and established cells lines (HEK 293 and Hep G2). We found that transfection efficiency was affected mainly by polymer/pDNA ratio and DNA concentration and in less extent by PEI MW. In bovine fibroblast, preincubation of PEI nanoparticles with fetal bovine serum (FBS) greatly increased percentage of cells expressing the transgene (up to 82%) while significantly decreased the polymer cytotoxic effect. 87 and 217 kDa PEI rendered the highest transfection rates in HEK 293 and Hep G2 cell lines (>50% transfected cells) with minimal cell toxicity. In conclusion, our results indicate that fully deacylated PEI of 87 and 217 kDa are useful DNA vehicles for non-viral transfection of primary cultures of bovine fetal fibroblast and HEK 293 and Hep G2 cell lines.